2003
DOI: 10.1161/01.atv.0000084639.16462.7a
|View full text |Cite
|
Sign up to set email alerts
|

TR3 Orphan Receptor Is Expressed in Vascular Endothelial Cells and Mediates Cell Cycle Arrest

Abstract: Objective-Endothelial cells play a pivotal role in vascular homeostasis. In this study, we investigated the function of the nerve growth factor-induced protein-B (NGFI-B) subfamily of nuclear receptors comprising the TR3 orphan receptor (TR3), mitogen-induced nuclear orphan receptor (MINOR), and nuclear orphan receptor of T cells (NOT) in endothelial cells. Methods and Results-The mRNA expression of TR3, MINOR, and NOT in atherosclerotic lesions was assessed in human vascular specimens. Each of these factors i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 33 publications
1
49
0
Order By: Relevance
“…The role of the Nur77 family in the proliferation of endothelial cells is also contradictory. Adenoviral overexpression of Nur77 in cultured endothelial cells resulted in cell-cycle arrest (Arkenbout et al, 2003). In contrast, Zeng et al (2006) showed that TR3/Nur77 is necessary and sufficient for VEGF-A-induced proliferation and survival of cultured HUVECs and for angiogenesis in vivo.…”
Section: -Mp Enhances Transcriptional Activity Of Hif-1a Y-g Yoo Et Almentioning
confidence: 95%
“…The role of the Nur77 family in the proliferation of endothelial cells is also contradictory. Adenoviral overexpression of Nur77 in cultured endothelial cells resulted in cell-cycle arrest (Arkenbout et al, 2003). In contrast, Zeng et al (2006) showed that TR3/Nur77 is necessary and sufficient for VEGF-A-induced proliferation and survival of cultured HUVECs and for angiogenesis in vivo.…”
Section: -Mp Enhances Transcriptional Activity Of Hif-1a Y-g Yoo Et Almentioning
confidence: 95%
“…Previous studies reported differing effects of manipulation of Nur77 levels in endothelial cells: Arkenbout et al (2003) found that overexpression of Nur77 decreased mitogenic responsiveness, whereas Zeng et al (2006) showed that Nur77 overexpression induced angiogenesis and Nur77 antisense inhibited VEGF-driven angiogenesis. Our results demonstrated that Nur77 siRNA was effective in suppressing VEGF-induced Nur77 mRNA expression and also markedly decreased VEGF-dependent cell proliferation, migration and tubulogenesis, although in contrast to Egr3 knockdown, Nur77 siRNA had little effect on basal or VEGF-dependent cell survival.…”
Section: Vegf Regulation Of Egr3 D Liu Et Almentioning
confidence: 99%
“…However, studies of Nur77 in endothelial cells have yielded differing results. Adenoviral overexpresion of Nur77 in human umbilical vein endothelial cells (HUVECs) caused cell cycle arrest (Arkenbout et al, 2003), whereas inhibition of Nur77 protein expression suppressed VEGF-induced angiogenesis .…”
Section: Introductionmentioning
confidence: 99%
“…In vascular smooth muscle cells, the expression of Nur77 and NOR-1 was significantly induced by atherogenic stimuli, such as platelet-derived growth factor-BB, epidermal growth factor, and ␣-thrombin. 8,9 Overexpression of Nur77 has been shown to inhibit cell proliferation and attenuate vascular injury-induced neointimal formation in vivo. 10,11 NR4A nuclear receptors are also induced in ECs by several stimuli, such as hypoxia, TNF-␣, and vascular endothelial growth factor, and modulate EC growth, survival, and angiogenesis.…”
mentioning
confidence: 99%